Typology of revolutions and Bibliologos - A. V. Sokolov (Библиосфера)
The objectives of the research are as follows: 1. To substantiate the content of the transdisciplinary concept “Bibliologos” and to demonstrate its use in library and book science. 2. To develop the historical periodization of the origin, formation and development of Bibliologos on the background of anthropological and intellectual revolutions from the paleolithic to the noosphere. 3. To outline the prospects for revolutionary transformations of humanity in the foreseeable future. The article proposes the typology of anthropological revolutions of the ancient world from the formation of the verbal language and writing to the emergence of Bibliologos during the axial time of world history. Intellectual revolutions of the mature bibliologos in the modern period are typologized. Two directions of intellectual transformations of Bibliologos of the New Age are considered: a cultural-humanistic one – the development of the humanistic content of book culture from the Renaissance to the crisis of humanism in the 20th century; a technological one – the development of the technical means of Bibliologos as a productive force in the form of four industrial revolutions and digital culture. Noosphere is presented as the environment of the human of the future conditioned by space evolution, formed by the post-industrial civilization and humanistic culture. The necessity of a humanistic revolution to overcome the anthropological crisis threatening the future of mankind has been substantiated. The creative function of Bibliologos in the formation of the noosphere is shown.As a result of the study, the author came to the following conclusions: 1) Bibliologos is defined as the collective intellect of a civilized society in the form of a productive force that ensures creation, preservation, and use of book culture. The subjects of Bibliologos are the professionals in the book and library services and science (practitioners, administrators, scientists, teachers), government and commercial figures, bibliophiles, printing engineers, and active readers. 2) Revolutionary creativity is divided into two classes: anthropological revolutions – active subjects abandon the old way of life, and a new type of person is formed; intellectual revolutions – a civilized society is going through a spiritual crisis and is being transformed into a cultural society of a new type. To overcome the anthropological crisis that threatens the future of mankind, a humanistic revolution is needed, aimed at creating the noosphere. 3) In the space of the noosphere, the mission of the bibliosphere is not limited to serving as a service subsystem in the structures of the institutions of education, science, culture, ideology, art, although it is, of course, necessary to satisfy current demands. The main pedagogical mission of the Bibliologos is to use his intellectual potential for the humanistic revolution in Russia and the education of the noospheric man – a man of a new anthropological type.